Associations between gastro-oesophageal reflux disease and a range of diseases: an umbrella review of systematic reviews and meta-analyses - Tan, JinJing (BMJ Open, 2020)
OBJECTIVE: Numerous meta-analyses have revealed the association between gastro-oesophageal reflux disease (GORD) and a range of diseases; however, the certainty of the evidence remains unclear. This study aimed to summarise and assess the certainty of evidence derived from meta-analyses. METHODS: Embase, PubMed, Web of Science, Cochrane Databases of Systematic Reviews, CNKI and Wangfang databases from their inception to 22 February 2020 were queried for systematic reviews and meta-analyses on the association between GORD and various diseases. The methodological quality of the included studies was assessed using A Measurement Tool to Assess Systematic Reviews 2 (AMSTAR 2), and evidence certainty was evaluated using the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) system. Statistical analysis was conducted using Stata V.15. RESULTS: Ten publications with associations between GORD and different types of diseases were included. There was high heterogeneity (I(2) >75%) among seven independent meta-analyses. Evidence for publication bias in two independent meta-analyses was also observed. According to the AMSTAR 2 approach, the methodological quality was high for 20% of meta-analyses, moderate for 10%, low for 40% and critically low for 30%. Based on GRADE approach, the certainty of evidence was high for the association between GORD and higher risk of chronic obstructive pulmonary disease (COPD) exacerbation (OR 5.37; 95% CI 2.71 to 10.64) and higher prevalence of oesophageal adenocarcinoma (OR 4.57; 95% CI 3.89 to 5.36), and it was moderate for the association between GORD and higher chronic rhinosinusitis prevalence (OR 2.16; 95% CI 1.37 to 3.48). CONCLUSION: The association between GORD and a range of diseases was extensively studied, and our findings revealed a high certainty of evidence of the association between GORD and an increased risk of COPD exacerbation as well as increased prevalence of oesophageal adenocarcinoma. Further investigations using systematic reviews and meta-analyses of high methodological quality that include prospective large cohort studies and adjusted confounders are warranted. PROSPERO REGISTRATION NUMBER: CRD42019122264.